Exercitar-se conversando ou treinar focado: estudo sobre técnicas de si entre participantes de academia ao ar livre e academia de ginástica e musculação em Santa Maria - RS - Oliveira, Diego Marafiga de (2016)
This thesis is based in an ethnografic research developed throughout twelve months with people who participate in two distinct genres of gyms in Santa Maria (RS): Outdoors Gym and Fitness Gym. This work has as its objective to analyze the activities done by people who exercise in both modalities as technologies of the self, from the concept discussed by Michel Foucault. Based on observations in the field, evident differences were found in the way the physical activities are done. Among the practitioners in the Outdoors Gym, the exercises are performed to treat an existing illness or to prevent a future illness, in this genre, physical activities are performed while talking and pleasantry exchanging, without the help of physical education professionals, which highlights sociability as a significant aspect of the use of this gym to these people. On the other hand, in Fitness Gyms, the physical activities are performed aiming to obtain a greater physical conditioning and body muscle, reflecting aesthetics concern. Physical exercise is done through professional body expertise knowledge, in which people do a series of training with the aim to maximize results in the gym. Therefore, research has identified the use of two models of gym, encouraged by different agents, as a way to influence personal behavior.